Chenia lorentzii (Müll. Hal.) R.H. Zander in Uruguay. - Suarez, Guillermo Martin (2012)
The genus Chenia is not included in the bryophyte checklist of Uruguay (Matteri, 2004), a country that remains among the bryologically least explored places in South America. Discovered during a recent revision of mosses collected in Montevideo was Chenia lorentzii (Müll. Hal.) R.H. Zander, a neotropical species. It is known previously from Argentina (Suárez et al., 2005; Cano & Gallego, 2008) and Bolivia (Churchill et al., 2009). This occurrence of C. lorentzii is a new record for the bryophyte flora of Uruguay, and the phytogeographical province of Pampa. The nearest other recorded for the species is in the phytogeographical province of Chaco (south of Bolivia and north-central of Argentina). The plants from Uruguay fit well within the concept of this species and are easily recognized by the dentate upper leaf margins, large, epapillose upper laminal cells and red coloration in KOH.